Clinician perspectives on cefpodoxime use in respiratory tract infections in India: results from a nationwide survey - Manjula S.; Krishna Kumar M. (International Journal of Advances in Medicine, 2026)
Background: Despite several clinical studies regarding the effectiveness of cefpodoxime in various infections, there is a dearth of studies among clinicians. So, this study aims to assess the perspectives of clinicians on the clinical use and perceived outcomes of cefpodoxime in respiratory tract infections (RTIs) in India. Methods: A cross-sectional study was conducted among clinicians practicing in routine clinical settings across India. A 22-question structured questionnaire was used to assess respiratory infection management, with a focus on cefpodoxime use, etiology, diagnostic approaches and clinical outcomes. Descriptive statistics were used to summarize responses as frequencies and percentages using Microsoft Excel. Results: Among 818 clinicians, 51% reported that lower RTIs (LRTIs) are the most commonly encountered infections in their clinical practice. More than half (58.92%) indicated prescribing cefpodoxime primarily for LRTIs. About 59% of respondents stated that both bacterial and viral etiologies contribute to upper RTIs (URTIs) in their practice. Around 53% identified chest X-ray as the most preferred diagnostic modality for Mycoplasma pneumoniae infection in adults. The majority (75.67%) reported cefpodoxime as the most commonly used antimicrobial agent for URTIs. A large proportion (85.82%) indicated cefpodoxime as the preferred oral drug for acute otitis media. Approximately 51% rated cefpodoxime as providing marked improvement on a 5-point global improvement scale. Conclusions: LRTIs are most prevalent in clinical practice, with cefpodoxime widely used across respiratory indications. Clinicians recognize mixed etiologies in URTIs and prefer chest X-ray for diagnosis. Cefpodoxime demonstrates high usage, favorable outcomes and marked clinical improvement, supporting its effectiveness and utility in routine RTI management.